The ANALISIS PEMELIHARAAN DAN KINERJA BOGIE KERETA TB-398: STUDI KASUS DI DEPO PASARTURI - Ahmad Dedy Agus Cahyono; Ilham Arifin (ENIGMA: Engineering in Green Machinery, 2025)
The bogie is a vital component in the train system that affects the comfort, stability, and safety of train operations. This paper discusses the technical specifications of the TB-398 train bogie and the maintenance strategies implemented at Pasarturi Depot to maintain the performance and safety of the train operations. Using the Failure Mode and Effect Analysis (FMEA) approach, this paper identifies critical components of the TB-398 bogie that require special attention in maintenance, such as wheel diameter, axle distance, and maximum axle load. Based on the FMEA analysis, maintenance priorities are determined for each component, focusing on preventive and predictive maintenance. The study shows that planned and periodic maintenance can reduce the risk of system failures and extend the operational lifespan of the TB-398 bogie. The findings provide valuable insights for train maintenance management to improve operational efficiency and safety at Pasarturi Depot.